Pemberdayaan Remaja Putri dalam Upaya Pencegahan Stunting - Immawanti, Immawanti; Pattola, Pattola; Wahyuddin, Munadiah; Laila, Ima; Aras, Fitrah Ramadhani (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Stunting remains a serious public health problem in Indonesia. It impacts children's physical growth and cognitive development and increases the risk of chronic diseases in adulthood. One of the main causes of stunting is a lack of knowledge about balanced nutrition and reproductive health from adolescence. Adolescent girls play a crucial role in stunting prevention efforts because they are potential mothers and directly determine the nutritional status of the next generation. Therefore, educating and empowering adolescent girls is a strategic step in breaking the chain of stunting in the community. Objective: This community service program aims to improve adolescent girls' knowledge and skills regarding balanced nutrition and reproductive health as a stunting prevention effort in Pangaliali Village, Banggae District, Majene Regency, West Sulawesi. Method: Implementation methods included program outreach, seminars and workshops on adolescent nutrition and reproductive health, and ongoing mentoring. Thirty adolescent girls aged 13–19 participated. Evaluation was conducted through pre- and post-assessment questionnaires to measure improvements in knowledge and adoption of healthy behaviors.. Result: The results showed an 85% increase in adolescent girls' knowledge and a 50% change in behavior toward adopting healthy eating patterns. The program's success was also supported by the use of educational media such as posters, learning modules, and the MAMMIS (Media Monitoring and Interactive Stunting) digital application as an interactive learning tool. These media were provided to adolescent girls as target partners in this community service activity. Conclusion: this community service program has proven effective in increasing the capacity of adolescent girls in stunting prevention. It is hoped that this activity will continue through the formation of adolescent cadres at the school level and become a program within the intra-school organization (OSIS) so that nutrition and reproductive health education efforts can be sustainable and contribute to reducing stunting rates.